Is a change in vocal loudness a first step towards becoming a medical doctor? (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY: Some evidence suggests that a loud voice is a core characteristic of medical professionals. It is unknown whether medical students talk louder than their non-medical peers and, if so, whether they commence their studies with a loud voice, representing a characteristic of admission, or whether sound pressure level changes during education, reflecting model learning. METHODS: We performed a cross-sectional observation study with 206 students (57% female), stratified in 4 groups (medical and non-medical students as freshmen and fifth-year students). Habitual loudness was defined as a student's sound pressure level, measured with a standardised sound level meter on basis of 2 vocal tasks. The hypothesis was tested in a 2-way analysis of variance, with year of study (first vs. fifth year) and field by study (medicine vs. non-medicine) as main factors. RESULTS: The sound pressure level of freshmen in medicine was, on average, 64.4 dB (SD 3.0), that of fifth-year medical students was 66.3 dB (3.7). The respective scores of non-medical students were 65.3 (SD 2.7) for freshmen and 64.0 (3.4) for fifth-year students, resulting in a significant interaction between field of study and years of study (F = 12.7; p = 0.0005). CONCLUSIONS: The findings of this preliminary study present some evidence that medical students, in contrast to their non-medical peers, learn to raise vocal loudness during their education in medical school. Habitual loudness of medical students, as a way to gain professional dominance and a possible risk for hoarseness in later life, deserves more attention.